The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/socsci11060262
|View full text |Cite
|
Sign up to set email alerts
|

Does Income Class Affect Life Satisfaction? New Evidence from Cross-Country Microdata

Abstract: This paper analyzes the impact of income class on subjective wellbeing. Using rich data from the Gallup World Poll, we investigate whether belonging to locally (both country- and time-specific) defined income classes influences individuals’ life satisfaction. We rely on a latent class analysis estimation method, using individual income proxied by household income divided by household size, as an observable characteristic to hypothesize the income classes. We fit a model with one categorical latent variable wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…to proxy social status (Connolly and Sevä 2018). We expect that respondents from higher social classes report higher life satisfaction, as shown by several previous studies (Yu and Blader 2020;Kaiser and Trinh 2021;Haddad et al 2022). The relationship between income and happiness was studied by Easterlin (1974; who showed that people with more income are, on average, happier, when considering within-country variation.…”
Section: H) Educational Levelmentioning
confidence: 90%
“…to proxy social status (Connolly and Sevä 2018). We expect that respondents from higher social classes report higher life satisfaction, as shown by several previous studies (Yu and Blader 2020;Kaiser and Trinh 2021;Haddad et al 2022). The relationship between income and happiness was studied by Easterlin (1974; who showed that people with more income are, on average, happier, when considering within-country variation.…”
Section: H) Educational Levelmentioning
confidence: 90%